Commentary: Thinking through Public Health Genomics. - Rapp, Rayna (Medical Anthropology Quarterly, 2013)
The author discusses perspectives related to public health genomics, medical anthropology, and science studies. Topics include the role of for-profit innovations in re-creating personal risk profile for diseases and drug metabolism, an interview by periodical editor Sandra Lee with consumers of genetic testing company 23&Me, and the use of admixture technologies in probing DNA samples.